Restoring structural parameters of lipid mixtures from small‐angle X‐ray scattering data. Issue 1 (16th January 2021) - Konarev, Petr V.; Gruzinov, Andrey Yu.; Mertens, Haydyn D. T.; Svergun, Dmitri I.
Abstract : An approach to restore the structural parameters of lipid mixtures from small‐angle X‐ray scattering data is developed. Abstract : Small‐angle X‐ray scattering (SAXS) is widely utilized to study soluble macromolecules, including those embedded into lipid carriers and delivery systems such as surfactant micelles, phospholipid vesicles and bilayered nanodiscs. To adequately describe the scattering from such systems, one needs to account for both the form factor (overall structure) and long‐range‐order Bragg reflections emerging from the organization of bilayers, which is a non‐trivial task. Presently existing methods separate the analysis of lipid mixtures into distinct procedures using form‐factor fitting and the fitting of the Bragg peak regions. This article describes a general approach for the computation and analysis of SAXS data from lipid mixtures over the entire angular range of an experiment. The approach allows one to restore the electron density of a lipid bilayer and simultaneously recover the corresponding size distribution and multilamellar organization of the vesicles. The method is implemented in a computer program, LIPMIX, and its performance is demonstrated on an aqueous solution of layered lipid vesicles undergoing an extrusion process. The approach is expected to be useful for the analysis of various types of lipid‐based systems, e.g. for the characterization of interactions between target drug molecules and potential carrier/delivery systems.